Reformulation of the Indonesian Sharia Security System: Integration of Rahn Institutions with Preferential Rights and Droit de Suite - Zuwanna Corna Gumanti; Henry Soelistyo Budi; Hayyan Ul Haq (Jurnal Greenation Sosial dan Politik, 2026)
This study aims to formulate a reformulation of the Rahn concept as an instrument and institution of Sharia security that is capable of providing legal certainty without compromising Sharia principles. The method employed is normative legal research, utilizing both statutory and conceptual approaches. The results of the study indicate that Rahn has not been recognized as a property right in positive law and therefore does not have preferential rights, the principle of droit de suite, and executive power, which impacts low legal certainty and limited use in Sharia financing. Therefore, it is necessary to reformulate Rahn as a form of hybrid security right that allows for limited recognition of property rights through registration regulations, strengthens the legal standing of third parties, and establishes an execution mechanism based on Sharia principles. This reformulation is expected to bridge the gap between sharia law and positive law, thereby increasing the effectiveness of the sharia financing system in Indonesia.